A 0.6V, 8.4uW AFE circuit for biomedical signal recording. (May 2018) - Chen, Chengying; Chen, Liming; Wang, Xinghua; Zhang, Feng
Abstract: For the detection of biomedical signal in wearable health devices, in this paper a fully-integrated, low-power, low-noise analog front-end (AFE) circuit is proposed. The AFE circuit includes a fully-differential amplifier with high-pass characteristics and a 14bit/500 Hz Sigma-Delta modulator based on cascode inverter. The fully-differential amplifier increases the output swing and improves the signal to noise ratio (SNR). Inverter-based Sigma-Delta modulator using bootstrapped switch completes high accuracy signal sampling in low supply voltage and finally outputs digital code. Two subthreshold bandgaps provide stable bias current and reference voltage for amplifier and Sigma-Delta modulator respectively. The circuit is fabricated with SMIC 0.13 μm CMOS mixed-signal technology occupying area of 1.68 mm 2 . The measurement results show that when the power supply voltage is 0.6 V, the input referred voltage noise of amplifier is 3.976μVrms and noise efficient factor (NEF) is 3.658. The maximum signal to noise and distortion ratio (SNDR) of AFE is 66.7 dB with only 8.4μw power consumption. Compared with the previous references, it has the maximum SNDR among them.